Strategic Business Unit And Organizational Performance: Theoretical Approach - Mebirouk, Mohamed Bachir; Beldjazia, Omar (جامعة الوادي - University of Eloued, 2016)
The aim of this study was to determine the extent of the participation strategic business unit to improve the performance of the organization, and in the composition of added value, and this requires a kind of continuous assessment in the light of specific criteria to measure the performance of the strategic business unit during each application and strategy unit of the organization. And linked to the process of businesses assessment strategy through the organization determine the extent of participation of business strategy for each unit configures value-added strategy college of the organization by achieving a competitive advantage.Where the focus in this study on the competitive strategies of Porter’s (cost leadership strategy, differentiation strategy, focus strategy). هدفت هذه الدراسة إلى تحديد مدى مشاركة وحدة الأعمال الاستراتيجية في تحسين أداء المنظمة، وفي تكوين قيمة مضافة, وهذا يتطلب وجود نوع من التقييم المستمر في ضوء معايير محددة لقياس أداء استراتيجية الأعمال أثناء التطبيق في كل وحدة استراتيجية تابعة للمنظمة. وترتبط عملية تقييم استراتيجيات الأعمال باستراتيجية المنظمة من خلال تحديد مدى مشاركة استراتيجية الأعمال لكل وحدة استراتيجية بتكوين قيمة مضافة كلية للمنظمة عن طريق تحقيق ميزة تنافسية. حيث تم التركيز في هذه الدراسة على الاستراتيجيات التنافسية العامة لبورتر( استراتيجية قيادة الكلفة، استراتيجية التمايز، استراتيجية التركيز).
مقال
Keywords: استراتيجية وحدة الأعمال، الاستراتيجية التنافسية، الأداء التنظيمي; strategic business unit, competitive strategy, organizational performance